2014
DOI: 10.5539/ijbm.v9n11p92
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the Spiritual Leadership Model in the Healthcare Industry in Iran

Abstract: The purpose of the present research is to test the spiritual leadership model in the Iranian healthcare industry. The research takes a quantitative approach involving the distribution of 143 questionnaires to different professionals in healthcare centers in Tehran, Iran. Spiritual leadership creates an intrinsic motivation to achieve organizational outcomes. It is a function of seven dimensions: vision, hope/faith, altruistic love, meaning/calling, membership, commitment, and productivity. The authors conduct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Ashmos and Duchon, 2000; Mohamed and Wisnieski, 2004; Moore and Casper, 2006; Gotsis and Kortezi, 2008). Other studies have examined the effects of spirituality on work-related outcome variables such as job satisfaction, work participation, organizational commitment, organizational identification, intention to quit smoking, organization-based self-esteem, organizational frustration, satisfaction with work rewards and organizational performance (Abdizadeh and Khiabani, 2014; Milliman et al. , 2003; Duchon and Plowman, 2005; Kolodinsky et al.…”
Section: Workplace Spirituality (Wps)mentioning
confidence: 99%
See 1 more Smart Citation
“…Ashmos and Duchon, 2000; Mohamed and Wisnieski, 2004; Moore and Casper, 2006; Gotsis and Kortezi, 2008). Other studies have examined the effects of spirituality on work-related outcome variables such as job satisfaction, work participation, organizational commitment, organizational identification, intention to quit smoking, organization-based self-esteem, organizational frustration, satisfaction with work rewards and organizational performance (Abdizadeh and Khiabani, 2014; Milliman et al. , 2003; Duchon and Plowman, 2005; Kolodinsky et al.…”
Section: Workplace Spirituality (Wps)mentioning
confidence: 99%
“…. Other studies have examined the effects of spirituality on work-related outcome variables such as job satisfaction, work participation, organizational commitment, organizational identification, intention to quit smoking, organization-based self-esteem, organizational frustration, satisfaction with work rewards and organizational performance(Abdizadeh and Khiabani, 2014;Milliman et al, 2003;Duchon and Plowman, 2005;Kolodinsky et al, 2008;Rego and Cunha, 2008;Pawar, 2009;Nicolaides, 2018;Biswakarma, 2018;Otaye-Ebede et al, 2019).Management must promote WPS to maintain employee productivity, which has been created through SL(Widyanti and Basuki, 2021) Widodo and Suryosukmono's (2021). study also showed that both SL and WPS affect the purposeful work of government employees, including health service employees.…”
mentioning
confidence: 99%
“…3 , 4 A leader should “see others”, which means pay attention to the needs and interests of employees he/she manages and take care of their well-being. 5 , 6 A leader should also integrate various viewpoints – his/her own, employees’ own and organizational perspectives, and look out for an integrated solution. 4 A leader without integrative awareness and driven by fear is ineffective.…”
Section: Introductionmentioning
confidence: 99%
“…Spiritual leadership has recently attracted the attention of Iranian researchers in health-care system and has been investigated in various research domains. Hence, it is necessary to assess the status of spiritual leadership in nursing (10)(11)(12). Today, this type of leadership has led to great outcomes for nursing managers and nurses.…”
Section: Introductionmentioning
confidence: 99%
“…Instrument psychometric process ensures the scholars and researchers of the validity and generalizability of the findings of the study (20). In the studies carried out in Iran in the nursing field to examine the correlation between spiritual leadership and its individual and organizational consequences, the researchers have studied areas of Fry's questionnaire, yet, none of them has performed the localization and psychometrics of the entire instrument (12,19,21).…”
Section: Introductionmentioning
confidence: 99%